(untitled) (Transport systems and technologies, 2018)
There is a marked tendency in the railway transport of Ukraine to increase the number of traffic safety violations associated with freight wagons. The main reason for the reduction of reliability are the peculiarities of the design of wagons and the imperfection of its individual parts, as well as the system of planned and current types of repairs. In this regard it is important to increase the reliability of nodes and parts of wagons in operation. Solving the problem of reducing the reliability of rolling stock is possible through the modernization of existing equipment, as well as the introduction of innovative technical tools that have improved reliability. The main factor in adhering to the basic properties of the reliability of any object is its durability. Indicators of durability directly depend on the life of the main elements of the car. The article proposes an improved design of the boot knot, which is capable of providing a rational perception of the combined load, which leads to a significant improvement in the conditions of the bearings and increase their resource. The distribution of loads between rollers in a typical boot knot and upgraded is investigated. The above studies substantiate the expediency of taking measures to reduce the number of malfunctions of roller buses and freight wagons in general.